Non-Carious Cervical Lesions Restoration with Direct-Indirect Composite Resin Technique: Case Report: Non-Carious Cervical Lesions Restoration - Riyandhika Putra; Wandania Farahanny; Nevi Yanti (Universitas Syiah Kuala, 2025)
Non-Carious Cervical Lesions (NCCLs) are the loss of tooth structure in the cementoenamel junction. The etiology of NCCLs comprises stress, friction, and biocorrosion. The direct composite resin technique in NCCLs has challenges, including achieving a good gingival margin finish and patient discomfort during treatment. The direct-indirect composite resin technique has the advantage of minimizing challenges and optimizing the restoration. This case report describes NCCL's restorative treatment using a direct-indirect composite resin technique. Case report: A 28-year-old male has a chief complaint of a cavity in the cervical anterior teeth with sensitivity to cold and blackening. The patient has been smoking ten cigarettes a day. The patient was diagnosed with an abrasion lesion from vigorous brushing. A direct-indirect composite resin technique was used to restore the case. Discussion: Direct-indirect techniques have some advantages, such as achieving a good gingival margin finish and reducing patient discomfort during treatment. Extraoral finishing and polishing can be easy and can achieve ideal outcomes for restoration marginal adaptation. Polymerization shrinkage in composite resin can be reduced with additional extraoral light cure, even when insufficient curing occurs at the bottom of the cervical inlay. The direct-indirect composite resin technique provides a good restoration.